IDENTIFIKASI KANDUNGAN FITOKIMIA KULIT KAYU ALABAN (Vitex pubescens Vahl) BERDASARKAN KETINGGIAN TEMPAT (ELEVASI) DI KECAMATAN PELAIHARI, KABUPATEN TANAH LAUT - Ahdiyaka Jayasukma Pribadi; Gusti Abdul Rahmat Thamrin; Adi Rahmadi (Universitas Lambung Mangkurat, 2020)
The use of halaban bark as a raw material for natural-based medicines has enormous potential. This study aims to identify the phytochemical content in the form of flavanoids, tannins, steroids and triterpenoid alaban bark (Vitex pubescens Vahl) based on the height of the alaban tree. To find out the presence of active compounds contained in alaban bark, test samples were taken in the form of bark taken based on the difference in height of the place where alaban trees grew, namely low altitude, medium height and high altitude. The presence of the highest phytochemical content is found in tannin active compounds which show that all of the test samples are positively containing tannins. For flavonoid active compounds, of the entire test sample there were only 2 test samples which showed negative results, namely at low altitudes. Whereas the highest active steroid compound was found in the test sample at low altitude and the highest triterpenoid active compound was found in the test sample at high altitude.Keywords : Alaban; Tree bark; Phytochemicals; height of place